Identifying the enablers of Corporate Social Responsibility adoption in construction firms - Nassreddine Garoui; Saber Ibrahim (Discover Sustainability)
Abstract Corporate Social Responsibility (CSR) has become a vital organizational strategy, enhancing transparency, trust, and overall performance. Firms across various sectors are increasingly encouraged to adopt CSR initiatives. In the construction industry, known for its resource-intensive and hazardous activities, integrating CSR practices focused on sustainability, occupational health, and safety is particularly crucial. Despite its importance, limited studies have identified the key factors influencing CSR adoption in this sector. This study employs qualitative research methods to explore the factors shaping CSR practices in Saudi Arabian construction firms. Using the MICMAC technique, a hierarchical framework was developed to analyze the interactions among 18 identified variables, categorizing them into four groups based on their driving power and dependency. The analysis revealed that organizational culture and competitiveness are the most influential drivers of CSR adoption, while CSR communication, integration with corporate strategy, and managerial skills were found to be highly dependent factors. Human resource development and employee training also emerged as strong relay variables, highlighting their dual role in influencing and being influenced by other CSR factors. These findings underline the systemic and interrelated nature of CSR success factors in the construction sector. Finally, the study discusses the limitations of interpretive structural modeling and offers recommendations for future research, including the integration of dynamic modeling and broader stakeholder engagement.